Neurotoxin-Derived Optical Probes for Elucidating Molecular and Developmental Biology of Neurons and Synaptic Connections : Toxin-Derived Optical Probes for Neuroimaging - Bijjam, Rohini; Shorter, Susan; Bratt, Alison M; O'Leary, Valerie B; Ntziachristos, Vasilis; Ovsepian, Saak Victor (Molecular imaging and biology, 2024)
Botulinum neurotoxins (BoNTs) and tetanus toxin (TeTX) are the deadliest biological substances that cause botulism and tetanus, respectively. Their astonishing potency and capacity to enter neurons and interfere with neurotransmitter release at presynaptic terminals have attracted much interest in experimental neurobiology and clinical research. Fused with reporter proteins or labelled with fluorophores, BoNTs and TeTX and their non-toxic fragments also offer remarkable opportunities to visualize cellular processes and functions in neurons and synaptic connections. This study presents the state-of-the-art optical probes derived from BoNTs and TeTX and discusses their applications in molecular and synaptic biology and neurodevelopmental research. It reviews the principles of the design and production of probes, revisits their applications with advantages and limitations and considers prospects for future improvements. The versatile characteristics of discussed probes and reporters make them an integral part of the expanding toolkit for molecular neuroimaging, promoting the discovery process in neurobiology and translational neurosciences.
Keywords: tetanový toxin; neurozobrazování; Humans; synapse; Molecular Probes; neurotoxiny; botulotoxiny; lidé; zvířata; neurony; Neurotoxins; Botulinum Toxins; fluorescenční barviva; Fluorescent Dyes; Tetanus Toxin; Neurons; molekulární sondy; Animals; Synapses; Neuroimaging